Creative Education Management Strategy in Health Service Transformation : Electronic Medical Record Innovation at Kandou Manado General Hospital - Joulanda A. M. Rawis; Verry R. Palilingan; Nancy L. Sampouw; Ariel N. Rengkuan; Hartini Ngadiorejo; Lando E. Sumarauw; Renaldy J. Kalesaran (Badan Penerbit STIEPARI Press, 2025)
Along with technological advancements, the healthcare sector is increasingly encouraged to adopt digital systems to improve efficiency and service quality. This study aims to analyze the implementation and challenges of using the Electronic Medical Record (EMR) system at the Kandou General Hospital (RSUP) in Manado, as well as explore the perspectives of various parties involved in this digital transformation process. The main focus of this research is to explore the role of the Information Technology (IT) team, medical staff, and training staff in the successful implementation of the EMR system. This study adopts a qualitative approach, utilizing in-depth interviews and participatory observations as data collection methods. The results indicate that although the EMR system can improve efficiency in documenting and managing medical information, its implementation faces various technical challenges, such as the complex system integration and the limited capacity of IT human resources (HR). Furthermore, medical staff, particularly those less skilled in technology, face challenges in adapting to this system, especially during the transition period. On the other hand, training staff plays an important role in overcoming these obstacles through creative training approaches tailored to the specific work unit context. The study concludes that the success of EMR implementation heavily depends on effective training strategies, good coordination between the IT team and medical staff, and continuous technical support. The findings are expected to provide insights for hospital policies and relevant stakeholders in enhancing the adoption of digital technologies in the healthcare sector.